Trends in firearm injury in a southern California health care system from 2010 to 2020 - Margo Sidell; Sonya Negriff; Corinna Koebnick; Deborah Ling Grant; Claudia Nau; Hui Zhou; Rulin Hechter (BMC, 2023)
Abstract Background Firearm injury is a significant public health concern in the United States. Methods Data on fatal and nonfatal firearm injuries were obtained from a cohort of N = 7,473,650 members of Kaiser Permanente Southern California, a large integrated healthcare system between 2010 and 2020. Age-adjusted rates of combined fatal and nonfatal firearm injury per 100,000 members were calculated by year, with the 2010 US census as the reference population. Trends were evaluated using Poisson or negative binomial regression. Results There was an increasing trend in overall firearm injuries between 2010 and 2020 among adults in this large integrated healthcare system (p < .0001), primarily driven by non-self-inflicted firearm injuries (p < .0001). Self-inflicted injuries decreased during this time (p = .01). Injuries among youth showed no significant change. Conclusion There was an increasing trend in firearm injuries between 2010 and 2020 among adults in this large integrated healthcare system, primarily driven by non-self-inflicted firearm injuries; however, self-inflicted injuries decreased during this time. Injuries among youth showed no significant change.